XI JINPING DAN MOBILISASI SUMBER DAYA NASIONAL TIONGKOK: MODEL KEPEMIMPINAN TEKNOKRATIS DAN IMPLIKASINYA BAGI INDONESIA - Muh Saifudin khoiruzzamani; Sutarto, Tarsisius Susilo, Budi Saroso, Beny Leonard Limbong (INTELIGENSIA MEDIA, 2026)
President Xi Jinping’s leadership in China exemplifies a technocratic style focused on mobilizing the nation’s full spectrum of resources science and technology (S&T), industry, and high quality human capital to realize the China Dream, including military modernization. This paper examines how Xi’s technocratic leadership model integrates scientific capability and economic strength into defense strategy through a whole-of-nation approach such as Military-Civil Fusion (MCF), surging defense R&D investment, and military digital transformation. The core question is to what extent the synergy of research technology, defense industry human resources under Xi can inform the reformulation of Indonesia’s defense strategy and accelerate TNI’s digitalization. The study finds that amid Indo-Pacific competition, the ability to harness S&T comprehensively is a key determinant of defense superiority. Indonesia must learn from China’s approach, for example, by integrating research institutes, industries, and the military; boosting defense R&D; and building a TNI cyber force, to achieve a strategic leap toward Golden Indonesia 2045. Crucially, any such adaptation must be aligned with Indonesia’s Pancasila democracy and national context, ensuring that the defense strength built is not a threat to peace but a power to protect the nation.